Development Of Students’ Worksheet Oriented To Islamic Values Through Oncoming Material About Human Excretory - Harianti, Sapta Mala; Yusuf, Yusuf; Mukminah, Mukminah (Biota, 2022)
Teachers still employ irrelevant teaching material related to Islamic values during teaching and learning. They used the lecturing and question-and-answers methods. Thus, researchers developed teaching materials to make students happy and interested. This research entitled Development of Students’ Worksheet (LKPD) Oriented to Islamic Values through Oncoming Material about Human Excretory System in Class VIII of Junior High School/ Islamic Junior High School (SMP/MTs) to know the students’ responses to the work. The research problems were how to develop students’ worksheets (LKPD) oriented to Islamic values through the oncoming material about the human excretory system and how the students’ responses to LKPD that researchers made. This research was a development research that used the 4D research method. Products produced were categorized as valid not revised because of the validation of design to the tune of 78.12%, validation of subject matter experts to the tune of 70%, and subject matter from Islam experts to the tune of 80%. Meanwhile, the responses of 10 students indicated that four students were categorized as “worthy” to the tune of 94.44%, 83.33%, 100%, and 85.18%, while six students were classified as “quite worthy” with each percentage of 61.11%, 70.37%, 79.62%, 75.92%, 68.51%, and 75.92%.